Keutamaan Orang yang Berilmu dalam Al-Qur’an: Kajian Surah Al-Mujadalah Ayat 11 - Afra Amelia Azizah; Sarwadi Sulisno (Moral : Jurnal kajian Pendidikan Islam, 2025)
Education in Islam plays a vital role in developing human potential holistically, where knowledge serves as the primary indicator of an individual's quality. This study aims to examine the virtue of knowledgeable people from the Quranic perspective, focusing on the theological and pedagogical analysis of Surah Al-Mujadalah verse 11. The method employed is descriptive qualitative through library research with a thematic exegesis (tafsir) approach. The results indicate that QS. Al-Mujadalah verse 11 establishes a hierarchy of human dignity based on the integration of faith and knowledge, rather than social or material status. These findings confirm that the elevation of rank encompasses a worldly dimension in the form of moral authority and an otherworldly dimension in the form of high positions before Allah. The implications of this research for contemporary Islamic education emphasize the importance of eliminating the dichotomy between religious and general sciences to cultivate the insan kamil (perfect human), who possesses a balance of intellectual intelligence, spiritual depth, and social responsibility. The study concludes that the virtue of knowledge in Islam is always grounded in transcendental values that bridge theory, faith, and practical deeds.